Proceedings of the 11th Annual Conference on Genetic and Evolutionary Computation 2009
DOI: 10.1145/1569901.1569916
|View full text |Cite
|
Sign up to set email alerts
|

Evolving quorum sensing in digital organisms

Abstract: For centuries it was thought that bacteria live asocial lives. However, recent discoveries show many species of bacteria communicate in order to perform tasks previously thought to be limited to multicellular organisms. Central to this capability is quorum sensing, whereby organisms detect cell density and use this information to trigger group behaviors. Quorum sensing is used by bacteria in the formation of biofilms, secretion of digestive enzymes and, in the case of pathogenic bacteria, release of toxins or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The instruction set includes send-msg, msg-handler, and end-handler, whose functionality was discussed earlier. Various types of rotate instructions were tested [5], but the most effective were the single-step rotations, rotate-right and rotate-left, which enable an organism to rotate one cell to its right or left, respectively. Four different nop instructions were included (nop-A, nop-B, nop-C, and nop-X).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The instruction set includes send-msg, msg-handler, and end-handler, whose functionality was discussed earlier. Various types of rotate instructions were tested [5], but the most effective were the single-step rotations, rotate-right and rotate-left, which enable an organism to rotate one cell to its right or left, respectively. Four different nop instructions were included (nop-A, nop-B, nop-C, and nop-X).…”
Section: Methodsmentioning
confidence: 99%
“…The amount of energy conserved by a deme determined its fitness, as defined in Equation 3. In this section, we review the results of those experiments, including analysis of an evolved genome; additional details can be found in [5]. Of the 20 runs, 15 exhibited energy conservation, so the discussion focuses on those populations.…”
Section: Evolution Of Quorum Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prior study [12], we demonstrated that digital orProceedings of the Third IEEE International Conference on Self-Adaptive and Self-Organizing Systems, San Francisco, California, September 2009. (poster summary)…”
mentioning
confidence: 96%
“…In this study, we extend runs from [12] from 2, 500 deme generations to 5, 000 and observed 16 runs that evolved QS behavior. We then tested the robustness of the most abundant (dominant) genomes to the introduction of impaired mutants.…”
mentioning
confidence: 99%